High-Dose Corticosteroid Therapy for Erlotinib-Induced Interstitial Lung Disease in Japanese Patient with Advanced Pancreatic Cancer - Yoshioka, Masato; Watanabe, Go; Uchinami, Hiroshi; Ise, Norihito; Nakagawa, Yasuhiko; Kudoh, Kazuhiro; Morita, Ryo; Andoh, Hideaki; Yamamoto, Yuzo (JOP. Journal of the Pancreas, 2014)
Context Erlotinib is a selective epidermal growth factor receptor tyrosine kinase inhibitor used as a target therapy against non-small lung cancer and advanced pancreatic cancer. A regimen of erlotinib plus gemcitabine has been proven to prolong overall survival in the patient with advanced pancreatic cancer. In addition to common adverse effects, such as diarrhea, mucositis and skin rash (acne form eruptions), acute interstitial lung disease (ILD) has been reported as an infrequent but potentially fatal complication. We here report a case of a Japanese patient with erlotinib-induced ILD in whom high-dose corticosteroid therapy was successful. Case report A fifty-five-year-old male with cancer of the head of the pancreas with multiple liver metastases started treatment with gemcitabine plus erlotinib. On the 13th day of erlotinib treatment, he had high fever. Chest computed tomography (CT) scan showed a diffuse ground-glass like infiltration of both lungs. He was diagnosed with ILD, and high-dose corticosteroid therapy was started. Two weeks after the introduction of steroid therapy, the reticular shadow faded away on CT. He was successfully treated with corticosteroid for erlotinib-induced acute ILD although he died 6 months after the initiation of chemotherapy owing to disease progression. Conclusion we showed a case of a successfully treated Japanese patient of erlotinib-induced ILD. Because erlotinib-induced ILD would frequently occur in Japanese patients, closer attention to ILD should be paid for Japanese patients than in Western populations. If erlotinib-induced ILD occurs, a high-dose corticosteroid therapy would be a useful option of treatment. Image: Interstitial lung disease at chest CT.